Evaluation of the Function of Wild Animal Gut Microbiomes Using Next-Generation Sequencing and Bioinformatics and its Relevance to Animal Conservation. (May 2019) - Yao, Ran; Xu, Lianglaing; Lu, Guoqing; Zhu, Lifeng
The relationship between animal conservation and the animal gut microbiome is a hot topic in current microbial ecology research. Our group has recently revealed that the occurrence of diverse combinations of gut microbial compositions and functions (metagenomics) in Père David's deer ( Elaphurus davidianus ) populations is likely to lead to increased evolutionary potential and resilience in response to environmental changes. Thus, considering the effects of diet on the gut microbiome and the importance of a stable gut microbial community to host health, we suggest that a transitional buffer period (with feeding on a regular diet and a diet from the translocation habitat) is needed before animal translocation. When the gut microbiome enters into relatively stable stages and adapts to the new diet from the translocation site, the time is suitable for translocation. Long-term monitoring of the gut microbiomes of translocated animals (by collecting fresh feces and carrying out next-generation sequencing) is still necessary after their translocation.